2020
DOI: 10.3389/fnagi.2020.00130
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Atypical Clinical Characteristics of NOTCH3 Mutations Among Patients Admitted for Acute Lacunar Infarctions

Abstract: Objectives: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the most common hereditary small vessel disease, with reported frequencies of 2-5/100,000 individuals. Recently, it has been reported that some patients with NOTCH3 gene mutations show atypical clinical symptoms of CADASIL. Assuming that CADASIL is underdiagnosed in some cases of lacunar infarction, this study was designed to examine the prevalence of NOTCH3 gene mutations in the patients at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Recent genomic studies have shown that there are many more CADASIL patients than we expected 5 . Recently, Mukai et al reported the relationships between gene mutation types and clinical symptoms in Japanese CADASIL patients 6 .…”
Section: Discussionmentioning
confidence: 71%
“…Recent genomic studies have shown that there are many more CADASIL patients than we expected 5 . Recently, Mukai et al reported the relationships between gene mutation types and clinical symptoms in Japanese CADASIL patients 6 .…”
Section: Discussionmentioning
confidence: 71%
“… 39 Considering the strikingly high global and regional frequencies of pathogenic NOTCH3 mutations, CADASIL should no longer be recognized as a rare disease. In fact, NOTCH3 mutations have been identified in 5.6%–6.5% of Taiwanese patients with small-vessel-occlusion stroke, 38 40 3.5% of Japanese patients with acute lacunar infarction, 41 4% of patients with acute ischemic stroke in Jeju Island, South Korea, 42 and 0.5% of Caucasian patients younger than 70 years with lacunar infarction. 43 More attention should therefore be paid to NOTCH3 mutations as important risk factors for stroke in general populations.…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%
“…Sporadic VCI and CADASIL share underlying mechanisms such as blood-brain barrier disruption and white matter changes [41] . In addition, genetic and clinical studies have shown that CADASIL may be underdiagnosed in patients with mild clinical or radiological phenotypes [ 42 , 43 ]. In CADASIL, increased NOTCH3 activity mediates pathological changes in the structure of cerebral arteries, leading to a reduction in maximal dilator capacity of cerebral arteries and cerebral blood flow [44] .…”
Section: Clinical Application Of Am Into Vascular Cognitive Impairmentmentioning
confidence: 99%